Nikolay Petrovich Demichev - Astrakhan State Medical Academy, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article is dedicated to the memory of N.P. Demichev: Professor of the Department of Traumatology, Orthopaedics and Field Surgery of Astrakhan State Medical Academy, Doctor of Medical Science, member of the International Academy of Science, Honoured Doctor of the Russian Federation, Honourary Member of the Association of Orthopaedic Traumatologists of Russia and Bulgarian Society of Orthopaedic Traumatologists, member of the Union of Journalists and Union of Writers of Russia,  Honourary Freeman of Astrakhan.